Upaya Meningkatkan Kompetensi Guru Menggunakan Zoom Meeting untuk Pembelajaran Jarak Jauh di Sekolah Dasar - Caswita, Caswita (Jurnal Didaktika Pendidikan Dasar, 2022)
Background The problem raised in the research is the low competence of teachers in using the zoom meeting application for distance learning in implementing learning policies during the Covid-19 pandemic. Meanwhile, one of the teacher's tasks is to carry out creative and innovative learning in order to achieve maximum learning objectives under any conditions. The purpose of this study was to improve the competence of teachers using the zoom meeting application in distance learning through IHT at SDN 1 Tanjung Kec. Kawalu City of Tasikmalaya for the academic year 2021/2022. The research method used is experimental research with Pre Experimental Design type The One Group Pretest-Posttest Design. The results showed that the pretest of teacher competence reached 50% from the previous results of initial observations, only 30% were categorized as competent. Meanwhile, when the posttest reached 70% of the competent teachers, the indicators for the success of the research were 70% of all teachers. Based on the results of this study, it was concluded that competence in using the zoom meeting application for distance learning at SDN 1 Tanjung Kec. Kawalu City of Tasikmalaya can be improved through In House Training (IHT).